Two Phenolic Compounds from Chloroform Fraction of Syzygium Polycephalum MIQ. Stem Bark (Myrtaceae) - Tukiran Tukiran; Andika Pramudya Wardhana; Nurul Hidajati; Kuniyoshi Shimizu (Universitas Jenderal Soedirman, 2018)
Syzygium polycephalum (Kupa) is a plant of the Myrtaceae family which is one of the endemic plants in Indonesia, commonly called as Gowok. The chemical components of the plant have not been reported so far. This study is intended to know the molecular structures of isolated compounds of chloroform fraction from S. polycephalum stem bark.The steam bark of the plant is dried, powdered and macerated with methanol to yield methanolic extract. The methanolic extract was then conducted to fractionation using hexane and chloroform to obtain hexane and chloroform fractions. The chloroform fraction was further subjected to separation using column chromatography to obtain pure isolates and followed by measuring of their spectroscopic evidences. The isolation of chloroform fraction had led to the findings of two pure isolates. Their structures of isolates were elucidated by extensive spectroscopic methods and by comparison with the literature data to gain two phenolic compounds that are gallic acid and 3,4,3’-tri-O-methylellagic acid.